Edukasi Bahaya Demam Berdarah Dengue Dalam Kehidupan Sehari Hari Untuk Usia Anak dan Dewasa - Mira Agusthia; Margareta Desi Simatupang; Ester Tobing; Gizka Alifina; Lani Fitri (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2023)
Dengue Hemorrhagic Fever (DHF) is an illness caused by the Dengue virus, transmitted through the bite of the Aedes Aegypti mosquito. DHF can occur throughout the year and can affect all age groups, including pregnant women, children, and adults. Indonesia stands as a country with the highest mortality rates due to dengue fever cases in the Southeast Asian region. In certain areas, the rise in DHF cases is influenced by rainfall and air humidity. In some instances, the peak of DHF occurrences aligns with the peak of the rainy season. Hence, this research aims to educate the community about the dangers of and efforts in preventing the spread of Dengue Hemorrhagic Fever. The socialization method was implemented on December 6, 2023, at the Ananda Taman Raya Tahap 3 Integrated Health Service Post in Batam. The conducted activities revealed that the community has begun to be educated about preventing DHF and addressing it within the surrounding society.